Finite Element Analysis of Gyroid and Voronoi architectures of Porous 3D-Printed Ti-6Al-4V bone replacement materials - Ureña-Sandí, Noel Jacob (Universidad RWTH Aachen, 2022)
Titanium and titanium-based alloys are widely used as implants for bone replacement. However, the higher Young’s modulus of monolithic implants compared to the human bone’s causes a weakening of the surrounding bones, ultimately causing considerably high percentages of implant rejection. Porous materials reduce the Young’s modulus making it more comparable to the bones’. Finite Element simulations in COMSOL Multiphysics were used to perform simulations on Triply Periodic Minimal Surface (TPMS) gyroid, and stochastical Voronoi models generated in nTopology design software and compared with the compression results of Selective Laser Melting (SLM) manufactured compression samples. The simulations of unit cells accurately predicted the yield strength of the periodic gyroid materials for relative densities between 0.1 and 0.5, primarily when the porous plasticity Gurson model with void volume fraction between 0.05 and 0.1 was used. The prediction of the Young’s modulus showed an increasing divergence from the experiments with increasing relative densities. However, an empirical rule which also worked for the Voronoi family was developed to correct this divergence. Increasing the models’ size for the non-periodic Voronoi architectures proved to improve the accuracy of the yield strength prediction. The 0.5 relative density cube of 1.8 mm was large enough to be considered a Representative Volume Element (RVE) for this structure.
Proyecto de graduación (Maestría en Ingeniería Mecánica) Universidad RWTH Aachen. Facultad de Ingeniería Mecánica. Departamento de Continuum, 2022
Keywords: Análisis -- Elementos finitos; Arquitectura Gyroid; Materiales de reemplazo óseo; Arquitecturas Voronoi; Implantes; Aleaciones de Titanio; Simulación; Analysis -- Finite elements; Gyroid architecture; Bone replacement materials; Voronoi architecture; Implants; Titanium alloys; Simulation; Research Subject Categories::TECHNOLOGY::Engineering mechanics